How immigration may affect US native entrepreneurship: Theoretical building blocks and preliminary results - Harriet Orcutt Duleep; David A. Jaeger; Mark Regets (Institute for the Study of Labor (IZA), 2012)
This paper describes the theoretical underpinnings and provides empirical evidence for a model that predicts a positive impact of immigration on entrepreneurial activity. Immigrants, we hypothesize, facilitate innovation and entrepreneurship by being willing and able to invest in new skills. At the heart of this theoretical prediction is the observation that human capital not immediately valued in the U.S. labor market is useful for learning new skills. Because immigrants face a lower opportunity cost of investing in new skills or methods, this transfer of source-specific skills to the U.S. may lead immigrants to be more flexible in their human capital investments than observationally equivalent natives. Areas with large numbers of immigrants (even if they are not self-employed) may prove to be areas in which entrepreneurship and innovation are easier to accomplish. Our theory offers a unique perspective on the contributions of immigrants to economic development beyond traditional perspectives that focus on low-cost immigrant labor or immigrant entrepreneurship.
Keywords: J15; J24; J39; J61; L26; 330; immigration; innovation; entrepreneurship; human capital investment; skill transferability; opportunity cost; learning transferability; Migranten; Unternehmer; Innovation; Bildungsinvestition; Theorie; USA